Status of the names of some hydroid species (Cnidaria, Hydrozoa), described from the Atlantic coast of Patagonia - Miranda, Thaís P.; Cunha, Amanda F.; Marques, Antonio C. (Zootaxa, 2016)
Thirty new species of benthic leptothecate hydroids were described and named from Patagonia in a 1991 PhD dissertation by Mohamed El Beshbeeshy. Although constituting nomina nuda under provisions of the International Code of Zoological Nomenclature (ICZN), the names of some species were used in several scientific publications between 1991 and 2011. In 2011, the dissertation of El Beshbeeshy was published in accordance with Article 8 of the ICZN. Several species-group names appearing in that work nevertheless fail to fully comply with certain articles of the code. The goal of this contribution is to review the nomenclatural availability of the names of those 30 new taxa, and to clearly establish the current status of El Beshbeeshy’s material. Two of them were made available in 1999 as part of studies other than those of El Beshbeeshy, and correct authorship and date is here noted. Twenty-one of the nomina nuda were made available in a work published by El Beshbeeshy in 2011, although some constitute junior synonyms. Six of the new species-group names appearing in both the 1991 and 2011 works, established following a literature review of Patagonian species, were proposed without re-description, or designation of name-bearing types, or locations of such types. Most of them do not meet criteria of availability and remain nomina nuda. The status of each is discussed to avoid additional nomenclatural errors and continued taxonomic confusion.